Graphene wrapped NASICON-type Fe2(MoO4)3 nanoparticles as a ultra-high rate cathode for sodium ion batteries. (June 2016) - Sheng, Jinzhi; Zang, Han; Tang, Chunjuan; An, Qinyou; Wei, Qiulong; Zhang, Guobin; Chen, Lineng; Peng, Chen; Mai, Liqiang
Abstract: Na + superionic conductor (NASICON) type Fe2 (MoO4 )3 with capacious ion diffusion tunnels and a flat discharge plateau, is a promising cathode material for sodium ion batteries. However, the sluggish electrochemical kinetics limits its further development due to the poor electron conductivity and long Na + diffusion path. In this work, a graphene wrapped Fe2 (MoO4 )3 nanoparticle composite was synthesized via a micro-emulsion method followed by annealing. The composite exhibits ultra-high rate capability (64.1 mA h g −1 at 100 C, better than all the reported works) and good high-rate cycling stability (76% capacity retention after 100 cycles at 10 C). The enhanced electrochemical performances are attributed to the unique composite structure with shortened ion diffusion distance and high electron conductivity. Furthermore, the Na + insertion/extraction mechanism of the composite is systematically investigated, based on in-situ X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS). Our work demonstrates that the graphene wrapped Fe2 (MoO4 )3 nanoparticle composite has great potential for high-rate sodium ion batteries. Graphical abstract: Highlights: The Fe2 (MoO4 )3 nanoparticles are synthesized by micro-emulsion for the first time. The Fe2 (MoO4 )3 /graphene composite shows a high capacity of 64.1 mA h g −1 at 100 C. A solid solution reaction mechanism of Fe2 (MoO4 )3 is firstly proved by in-situ XRD.